Integrasi Public Relations dan Media sebagai Instrumen Komunikasi Efektif di Era Digital - Mareta Puri Rahastine; Susilowati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to analyze and develop a model of Public Relations and digital media integration as an effective communication instrument in the digital era. The library method is used to collect and analyze data through literature studies from books, journals, and trusted sources related to communication, public relations, and digital media. Data were collected from digital libraries and journal databases, then analyzed qualitatively by describing, criticizing, and synthesizing the contents of the literature. A comparative approach was applied to connect various views, resulting in a comprehensive understanding of the integration of Public Relations and media as an effective communication instrument in the digital era. The results of the study indicate that the integration of Public Relations and digital media functions greatly influences the effectiveness of organizational communication in the digital era. The role of PR has shifted to be more strategic with a focus on building image, reputation, and public trust in a sustainable manner. The use of digital media allows for fast, broad, and interactive communication, and supports real-time crisis management. This synergy also enhances transparent and participatory two-way communication, strengthening the organization's closeness to the audience.